2007
DOI: 10.1021/bi700508n
|View full text |Cite
|
Sign up to set email alerts
|

Redox Reactions of Copper Complexes Formed with Different β-Amyloid Peptides and Their Neuropathalogical Relevance

Abstract: The binding stoichiometry between Cu(II) and the full-length beta-amyloid Abeta(1-42) and the oxidation state of copper in the resultant complex were determined by electrospray ionization-Fourier transform ion cyclotron resonance mass spectrometry (ESI-FTICR-MS) and cyclic voltammetry. The same approach was extended to the copper complexes of Abeta(1-16) and Abeta(1-28). A stoichiometric ratio of 1:1 was directly observed, and the oxidation state of copper was deduced to be 2+ for all of the complexes, and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
271
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(303 citation statements)
references
References 91 publications
(305 reference statements)
30
271
2
Order By: Relevance
“…Results and Discussion Divergent reports of the electrochemistry of Aβ copper complexes have recently appeared (18)(19)(20). In the present study, we noticed that the cyclic voltamogramm of 0.2 mM Cu(Aβ) complex is strongly dependent of the peptide over copper ratio (Fig.…”
supporting
confidence: 47%
“…Results and Discussion Divergent reports of the electrochemistry of Aβ copper complexes have recently appeared (18)(19)(20). In the present study, we noticed that the cyclic voltamogramm of 0.2 mM Cu(Aβ) complex is strongly dependent of the peptide over copper ratio (Fig.…”
supporting
confidence: 47%
“…37,40 These latter species are expected to be particularly stable when both, His13 and His14, coordinate to the metal through the δ nitrogen of imidazole. 65 Computed SRP value for Ia is in very good agreement with the most recent experimental values determined for Cu 2+ -Aβ (1−16) complex (between 0.28 and 0.34V), 45,66,67 in accordance with the fact that this is the dominant species at pH ∼7.…”
Section: Standard Reduction Potential Calculationssupporting
confidence: 88%
“…40,41 It is worth mentioning that many experiments have also been done using the truncated Aβ (1-16) peptide, since it is more soluble than Aβ(1-42) and experimental evidences have shown that it can be very useful to understand its redox behavior, metal cation affinities, metal coordination and other physicochemical properties. 20,22,[42][43][44][45] Other truncated models such as Cu 2+ -Aβ(1-7) have been considered to study the mechanism of Cu 2+ reduction using quantum chemical methods, 37 but the interaction of Cu 2+ with larger systems including the whole Aβ(1-42) peptide have only been considered by means of classical molecular dynamic simulations. 46 The consideration of the full peptide Aβ(1-42) at the quantum mechanics level is computationally too expensive and thus, metal ion complexes are studied by using computational approaches that combine a quantum mechanical treatment for the copper coordination center and a molecular mechanics (MM) approach for the peptide moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity of Aβ oligomers can be attenuated in cultures by copper chelation [176,177]. The mechanism of copper-Aβ induced cytotoxicity might involve oxidative stress, as the complex catalytically generates hydrogen peroxide [178][179][180]. The binding of copper to Aβ is likely to be a factor in AD because copper, too, is enriched in amyloid plaque [82].…”
Section: Coppermentioning
confidence: 99%